Haben die knappen Weltersparnisse die US-Immobilienblase finanziert? - Fabian Lindner (Wirtschaft und Gesellschaft (WuG), 2014)
There is a consensus among the majority of economists that the credit supply is limited by current household saving. If governments or foreigners ran deficits, they would absorb this limited saving so that firms could not borrow any longer and had to reduce their investment. This is the "Loanable Funds" theory. Ben Bernanke's "Global Saving Glut" thesis is based on this view: according to Bernanke, the US depended on South Aast Asian and commodity exporting countries' scarce saving to finance the US real estate boom. Using simple accounting rules, the article shows however that credit is never limited by current saving. Often, the exact opposite it true: people can only save after others have taken on credit and paid incomes. This is also the case with the US and its trade partners and creditors: since non-Americans accept the US-Dollar as a means of payment, which only the US can produce, Americans give credit to themselves to finance their current account deficits. Each Dollar that non-Americans invest in the US has either been earned or borrowed in the US before. By their deficits, the US does not absorb scarce saving but allows other countries to increase their income and saving.
Keywords: 330